Warming accelerates termination of a phytoplankton spring bloom by fungal parasites. (21st October 2015) - Frenken, Thijs; Velthuis, Mandy; de Senerpont Domis, Lisette N.; Stephan, Susanne; Aben, Ralf; Kosten, Sarian; van Donk, Ellen; Van de Waal, Dedmer B.
Abstract: Climate change is expected to favour infectious diseases across ecosystems worldwide. In freshwater and marine environments, parasites play a crucial role in controlling plankton population dynamics. Infection of phytoplankton populations will cause a transfer of carbon and nutrients into parasites, which may change the type of food available for higher trophic levels. Some phytoplankton species are inedible to zooplankton, and the termination of their population by parasites may liberate otherwise unavailable carbon and nutrients. Phytoplankton spring blooms often consist of large diatoms inedible for zooplankton, but the zoospores of their fungal parasites may serve as a food source for this higher trophic level. Here, we investigated the impact of warming on the fungal infection of a natural phytoplankton spring bloom and followed the response of a zooplankton community. Experiments were performed in ca. 1000 L indoor mesocosms exposed to a controlled seasonal temperature cycle and a warm (+4 °C) treatment in the period from March to June 2014. The spring bloom was dominated by the diatom Synedra . At the peak of infection over 40% of the Synedra population was infected by a fungal parasite (i.e. a chytrid) in both treatments. Warming did not affect the onset of the Synedra bloom, but accelerated its termination. Peak population density of Synedra tended to be lower in the warm treatments. Furthermore, Synedra carbon: phosphorus stoichiometry increased during the bloom, particularly in the control treatments. This indicates enhanced phosphorus limitation in the control treatments, which may have constrained chytrid development. Timing of the rotifer Keratella advanced in the warm treatments and closely followed chytrid infections. The chytrids' zoospores may thus have served as an alternative food source to Keratella . Our study thus emphasizes the importance of incorporating not only nutrient limitation and grazing, but also parasitism in understanding the response of plankton communities towards global warming.